EFEKTIVITAS PEMBELAJARAN TUTOR SEBAYA DALAM PEMBELAJARAN AKUNTANSI BIAYA I - Nurkhin, Ahmad (Dinamika Pendidikan, 2013)
Implementation of bilingual classroom was the manifestation of internationalization vision of the institution (Unnes) to response to the progress of International Schools (SBI / RSBI). Cost Accounting I was a subject in bilingual class of FE Unnes in 2010/2011. The objective of the study was to explain the effectiveness of peer tutor learning method in Cost Accounting I in Bilingual Class. It was a class action research done in 2 months with 2 cycles. The type of peer tutor learning was tutor to student. The result of research showed that peer tutor learning method of Cost Accounting I in Bilingual Class of FE Unnes was effective. Studentsâ achievement increased significantly in the first and second cycle. It passes the effectiveness indicator which stated that at least 75% students could get 71. Thus, it is suggested that other types of peer tutor learning method can be investigated empirically for further researches in different designs.